2020
DOI: 10.2147/cia.s264987
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of an Alveolar Recruitment Maneuver During Lung Protective Ventilation on Postoperative Pulmonary Complications in Elderly Patients Undergoing Laparoscopy</p>

Abstract: Purpose: Controversy remains over whether alveolar recruitment maneuvers (ARMs) can reduce postoperative pulmonary complications. We hypothesized that performing an ARM in addition to lung protective ventilation (LPV) could improve intraoperative arterial oxygenation and postoperative pulmonary complications (PPCs) in elderly patients undergoing laparoscopy in the Trendelenburg position. Patients and Methods: Sixty-two patients (aged 65-85) scheduled for laparoscopic low anterior resection were randomized to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The reasons for the 183 exclusions were as follows: 105 were non-RCTs, 7 were non-adult studies, 18 reported open abdominal surgery, 13 did not report PPCs, 33 were animal experiments and 7 did not compare recruitment maneuvers to conventional mechanical ventilation. Finally, 17 RCTs with a total of 3480 patients were examined [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The details of the included studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for the 183 exclusions were as follows: 105 were non-RCTs, 7 were non-adult studies, 18 reported open abdominal surgery, 13 did not report PPCs, 33 were animal experiments and 7 did not compare recruitment maneuvers to conventional mechanical ventilation. Finally, 17 RCTs with a total of 3480 patients were examined [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The details of the included studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the completeness of the outcome data and lack of selective reporting, the risks of attrition bias and reporting bias were likewise evaluated as low. Five trials did not provide information on allocation concealment [ 18 , 26 , 28 , 31 , 32 ]. Twelve studies did not report the blinding of the outcome evaluators [ 15 , 18 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the incidence of PPCs was lower than previously reported in the Literatures [ 14 – 17 ]. This could be attributed to the small sample size, differences in inclusion criteria, with the prior LPVS trials including patients with acute respiratory distress syndrome (ARDS) [ 18 , 19 ], elderly patients [ 20 ], and patients undergoing thoracic surgery [ 21 ], versus the healthy lung patients in this study. Additionally, it is possible that the duration of mechanical ventilation was insufficient.…”
Section: Discussionmentioning
confidence: 99%